Methodology for assessment of learning management systems based on the impact of the assessed components - Blagoev, Ivaylo; Monov, Vladimir (Yearbook Telecommunications, 2018)
This article examines and classifies the individual requirements for the learning management systems, on the basis of which a subsequent assessment of the systems themselves could be carried out. The project analyzes the existing evaluation models based on an optimized methodology tailored to the degree of impact of each individual evaluation criterion and the specific type of the training organization implementing the training management systems. A scale for assessing the impact of individual criteria on the different types of organizations and a scale for assessing the compliance of the evaluated content management system with the individual criteria has been developed.